Internalisasi Nilai-Nilai Moderasi Beragama dalam Pembelajaran Sejarah Kebudayaan Islam: Studi Kasus pada Mahasiswa Pendidikan Agama Islam - Jamain Warwefubun; Nafila J.N; Alfian Jamal (Universitas Islam Negeri (UIN) Salatiga, 2025)
This study aims to examine the internalization of religious moderation values in the learning of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) among Islamic Education (PAI) students of the 2023 cohort. The research employs a qualitative approach, with data collected through in-depth interviews involving 12 informants, consisting of 10 students and 2 lecturers of the Islamic Cultural History course who are directly involved in the learning process. The findings indicate that the SKI course plays a significant role in introducing and internalizing wasathiyah values, such as tolerance, respect for diversity, and an inclusive attitude in religious life. Moreover, the internalization process is also influenced by student interactions and the lecturers’ teaching methods, which emphasize dialogue and open discussion. The integration of wasathiyah values into the SKI curriculum serves as a strategic effort to shape younger generations to be more open-minded, tolerant, and capable of appreciating differences within a pluralistic societ